Surufatinib plus toripalimab combined with etoposide and cisplatin as first-line treatment in advanced small-cell lung cancer patients: a phase Ib/II trial - Yaxiong Zhang; Yan Huang; Yunpeng Yang; Yuanyuan Zhao; Ting Zhou; Gang Chen; Shen Zhao; Huaqiang Zhou; Yuxiang Ma; Shaodong Hong; Hongyun Zhao; Li Zhang; et al. (Signal Transduction and Targeted Therapy, 2024)
Abstract There is still room for improvement in first-line treatment of advanced small cell lung cancer (SCLC). This trial firstly investigated efficacy and safety of antiangiogenic therapy (surufatinib) (200 mg, qd, po) plus anti-PD-1 treatment (toripalimab) (240 mg, d1, ivdrip) combined with etoposide (100 mg/m², d1-d3, iv, drip) and cisplatin (25 mg/m², d1-d3, ivdrip) for advanced SCLC as first-line treatment, which has been registered on ClinicalTrials.gov under the identifier NCT04996771. The four-drug regimen was conducted q3w for 4 cycles with maintenance therapy of surufatinib and toripalimab. The primary endpoint was progression-free survival (PFS). The secondary end points included objective response rate (ORR), disease control rate (DCR), overall survival (OS) and safety. All of the 38 patients were enrolled for safety analysis, while only 35 patients were enrolled for efficacy analysis since loss of efficacy evaluation in 3 cases after treatment. After a median follow-up of 21.3 months, the ORR was 97.1% (34/35), and the DCR and the tumor shrinkage rate were both 100% (35/35). The median PFS was 6.9 months (95% CI: 4.6 m–9.2 m) and the median OS was 21.1 months (95% CI: 12.1 m–30.1 m). The 12-month, 18-month, and 24-month OS rates were 66.94%, 51.39% and 38.54%. The occurrence rate of grade ≥3 treatment-emergent adverse events (TEAEs) was 63.2% (24/38), including neutrophil count decreased (31.6%, 12/38), white blood cell count decreased (23.7%, 9/38) and platelet count decreased (10.5%, 4/38). No unexpected adverse events occurred. This novel four-drug regimen (surufatinib, toripalimab, etoposide plus cisplatin) revealed impressive therapeutic efficacy and tolerable toxicities.